2007
DOI: 10.1029/2006jd007341
|View full text |Cite
|
Sign up to set email alerts
|

National Lightning Detection Network (NLDN) performance in southern Arizona, Texas, and Oklahoma in 2003–2004

Abstract: [1] Four field campaigns were conducted in southern Arizona (AZ) and in northern Texas and southern Oklahoma (TX-OK) in 2003 and 2004 to evaluate the performance of the U.S. National Lightning Detection Network TM (NLDN) in detecting cloud-to-ground (CG) lightning after an upgrade in 2002 and 2003. The 2-year average flash detection efficiency (DE) in AZ was 93% (1024/1097), and the measured (first plus subsequent) stroke DE was 76% (2746/3620). The corresponding values in TX-OK were 92% (338/367) and 86% (75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
229
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(236 citation statements)
references
References 17 publications
(32 reference statements)
7
229
0
Order By: Relevance
“…As a result, the estimated LA of an LLS based on lightning strikes to towers is expected to be somewhat better than that for natural lightning. On the other hand, the LLS location error determined from video data of strokes in the same channel is an upper limit because the return stroke channel is not always seen all the way down to the ground strike point of each return stroke (Biagi et al, 2007). Keeping in mind those specific limitations of tower measurements and VFRS recordings, the agreement between LA determined from GBT data and VFRS data in Austria is almost perfect.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As a result, the estimated LA of an LLS based on lightning strikes to towers is expected to be somewhat better than that for natural lightning. On the other hand, the LLS location error determined from video data of strokes in the same channel is an upper limit because the return stroke channel is not always seen all the way down to the ground strike point of each return stroke (Biagi et al, 2007). Keeping in mind those specific limitations of tower measurements and VFRS recordings, the agreement between LA determined from GBT data and VFRS data in Austria is almost perfect.…”
Section: Discussionmentioning
confidence: 86%
“…Due to the reason that almost no positive flashes with multiple strokes in the same channel exist, the LA is determined with negative flashes only. The method to estimate the LLS LA, based on multi-stroke flashes, is described in Schulz et al (2012) and Biagi et al (2007). As mentioned in Schulz et al (2012) this method does not show any systematical location error.…”
Section: Location Accuracymentioning
confidence: 99%
“…The detection efficiency since 1999 on cloud to ground flashes is 98 %. This makes it one of the best-performing LLS worldwide (ALDIS 2009;Anderson 2002;Biagi et al 2007;Castedo-Dorado et al 2011;Diendorfer 2007;Outcalt 2008;Podur et al 2003). The first detection sensor was put into operation in 1991, and archived lightning data are available since 1993.…”
Section: Austrian Lightning Detection and Information System Lightninmentioning
confidence: 99%
“…Because ALDIS detects around 98 % of all CG flashes in Austria (Diendorfer 2007), it was assumed that lightning could not have been the cause of the forest fire, if there were no flashes detected within the relevant time period. Single positive flashes under 10 kA were excluded from the analysis too, even if they were the nearest events, because studies have shown that these flashes are mostly (more than 90 %) CC and not CG lightnings (Biagi et al 2007;Diendorfer 2007;Hall and Brown 2006). Additionally, the probability for each lightning flash was estimated by the location accuracy of a specific flash (error ellipse).…”
Section: Decision Tree and Decision Matricesmentioning
confidence: 99%
See 1 more Smart Citation